PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL THINK TALK WRITE (TTW) DI KELAS V SDN 24 PARUPUK TABING KOTA PADANG - Zhafira, Alifiya; Azmi Alwi, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted because the narrative text writing skills of fifth-grade students at SDN 24 Parupuk Tabing, Padang City are still low. This is caused by the learning method that still prioritizes teachers, less active student participation, and the implementation of writing stages that are not optimal. The purpose of this research is to improve students' narrative text writing skills by using the Think Talk Write (TTW) learning model. This research uses the Classroom Action Research (CAR) method with qualitative and quantitative approaches. The research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. To collect data, observation, test, and non-test techniques were used. The research subjects included class teachers as observers, researchers as practitioners, and fifth-grade students as participants. The results of the study showed improvements in various aspects. In cycle I, the assessment of the teaching module in cycle I obtained 90% (SB) and increased in cycle II to 95% (SB). The assessment of the teacher aspect reached 82.5% (B) and increased to 95% (SB) in cycle II. Meanwhile, the assessment of the student aspect in cycle I was 82.5% (B) and also increased to 95% (SB) in cycle II. The average narrative text writing skills of students in cycle I was 77.87% (C), and increased to 88.31% (B) in cycle II. Thus, the Think Talk Write (TTW) learning model can improve the narrative text writing skills of fifth grade students of SDN 24 Parupuk Tabing, Padang City.